Intestinal Obstruction Caused by Gallstone Ileus. A Case Presentation - Mayquel Monzón Rodríguez; Lidia Torres Ajá; Nancy Capín Sarría (Medisur)
Gallstone ileus is the mechanical obstruction of the digestive tract caused by the impact of a calculation in the intestinal lumen. It is a rare complication of gallstones occurring in only 0.1% of patients. The case of a female, 89 years old patient suffering from diabetes, hypertension and a heart condition, who attended the Surgery Emergency Service of the Hospital for abdominal pain and vomiting is presented. Through physical examination and complementary radiological tests it was detected the presence of a mechanical intestinal obstruction for which the patient underwent emergency surgery. As the cause of occlusion it was found a thick gallstone in a jejunal loop. The patient progressed satisfactorily and was discharged 5 days after surgery.